Reducing Subcontractor Progress Monitoring Time on Multifamily Building Finishes Using a BIM-Based Procedure - Bazán, Darwin (2025)
In multifamily project construction, specialty subcontracting is common, but monitoring subcontractors, especially during finishing, presents significant challenges due to manual methods that are time consuming, make it difficult to detect deviations, and result in cost overruns and delays. This research proposes an automated monitoring procedure using a BIM model that integrates tools such as Revit, Navisworks, MS Project and Trimble Connect. The methodology includes four stages: analysis of information through surveys, identification of the traditional procedure in three companies, development of the new automated approach and validation in a pilot project. The results show a 42.4% reduction in daily monitoring time for subcontractors and a 41.4% reduction for technical personnel, in addition to improved access to real-time information. This optimizes coordination, reduces errors and ensures compliance with deadlines, significantly improving resource management in multifamily projects.